Cross-sectoral pollution externalities and multiple equilibria. (21st June 2019) - Karp, Larry; Paul, Thierry
Abstract: In familiar models, a decrease in the friction facing mobile factors (e.g., lowering their adjustment costs) increases a coordination problem, leading to more circumstances where there are multiple equilibria. We show that a decrease in friction can decrease coordination problems when a production externality arises from a changing stock, e.g. of pollution or knowledge. In general, the relation between the amount of friction that mobile factors face and the likelihood of multiple equilibria is non-monotonic.